A noteworthy new species of Peritassa (Celastraceae, Hippocrateoideae) from Amazonian Brazil - Lombardi, Julio Antonio [UNESP] (Missouri Botanical Garden Press, 2007)
The new species Peritassa manaoara Lombardi differs from other species in Peritassa Miers by its unique 3-lobed stigma. The inclusion of this new taxon in Peritassa was based on the characteristics of non-confluent anther locules and the disc free from the ovary wall, which distinguishes this species from Tontelea Aublet, the only other genus of Neotropical Hippocrateoideae species with a 3-lobed stigma and tubular nectariferous disc.
Keywords: Amazon basin; Brazil; Celastraceae; Hippocrateoideae; IUCN Red List; Peritassa